El neuromanagement como herramienta gerencial que fortalece la inteligencia emocional (2020)
This degree paper aims to demonstrate that Neuromanagement is the managerial tool that 21st century organizations need to manage in different processes and strengthen skills such as decision-making, strategic planning, adaptation to change, interpersonal relationships, communication, creativity and innovation. Furthermore, at the end of the work, the reader is expected to understand how Neuromanagement develops and strengthens the Emotional Intelligence of business leaders and their work teams.